Strategi Komunikasi Pemasaran Wisata Religi Berbasis Islamic Marketing dalam Peningkatan Pendapatan UMKM di Kawasan Makam Sunan Pojok Blora - Siti Krisdayanti; Imam Ali Bashori; Mohammad Irfani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to examine the marketing communication strategies of religious tourism based on Islamic marketing principles and their contribution to increasing the income of micro, small, and medium enterprises (MSMEs) in the Sunan Pojok Tomb area in Blora. This research employs a qualitative approach with a case study design. Data were collected through observations, interviews with MSME actors and tourism managers, and documentation related to tourism activities and local economic practices in the surrounding area. The findings indicate that the marketing communication strategies of religious tourism are implemented through word-of-mouth promotion, the use of social media, the organization of religious events, and the provision of friendly and ethical services to visitors. These strategies reflect the application of Islamic marketing values, including honesty (ṣidq), trustworthiness (amanah), good service (khidmah), and a spirit of social solidarity (ukhuwah). The implementation of these strategies contributes to an increase in tourist visits, which in turn expands the consumer base, encourages product diversification, and improves the income of MSMEs operating around the Sunan Pojok religious tourism area in Blora.